A four-limb parallel Schönflies motion generator with full-circle end-effector rotation. (April 2020) - Wu, Guanglei; Lin, Zirong; Zhao, Wenkang; Zhang, Sida; Shen, Huiping; Caro, Stéphane
Highlights: A four-limb parallel Schönflies motion generator with full-circle end-effector rotation. Singularity loci are identified graphically and numerically. A super-ellipsoidal workspace free of singularity suitable for pick-and-place application. Operation modes are identified for singularity avoidance. Abstract: This paper presents a four-limb parallel Schönflies motion generator for the pick-and-place application, whose end-effector is composed of a planetary gear train as the amplification mechanism to realize the full-circle rotation. The kinematic aspects, including the workspace, dexterity and singularity, are analyzed and evaluated. The singular configurations and the singularity loci are identified both graphically and numerically, which shows that the singular configurations of the manipulator can be avoided by keeping all the limbs working in a prescribed working mode together with the end-effector rotation in a clockwise direction from the neutral orientation. Moreover, the dexterity evaluation is carried out to depict the workspace quality and dexterous working envelope. It turns out that the proposed robot admits a super-ellipsoidal workspace with the full-circle rotation of the end-effector, suitable for pick-and-place operations. Finally, robot dynamics is considered to select the actuators.